Precision USPIO-PEG-SLex Nanotheranostic Agent Targeted Photothermal Therapy for Enhanced Anti-PD-L1 Immunotherapy to Treat Immunotherapy Resistance - Li T; Guo L; Li J; Mu X; Liu L; Song S; Luo N; Zhang Q; Zheng B; Jin G (International Journal of Nanomedicine, 2024)
Ting Li,1,* Lianshan Guo,2,* Jiaxu Li,3,* Xingyu Mu,4 Lijuan Liu,1 Shulin Song,1 Ningbin Luo,1 Qi Zhang,5 Bin Zheng,1 Guanqiao Jin1 1Department of Radiology, Guangxi Medical University Cancer Hospital, Nanning, 530021, People’s Republic of China; 2Department of Emergency, The Second Affiliated Hospital of Guangxi Medical University, Nanning, 530007, People’s Republic of China; 3Guangxi Key Laboratory of Natural Polymer Chemistry and Physics, College of Chemistry and Materials, Graduate School, Nanning Normal University, Nanning, 530001, People’s Republic of China; 4Department of Nuclear Medicine, Affiliated Hospital of Guilin Medical University, Guilin, 541001, People’s Republic of China; 5Laboratory Animal Center, Guangxi Medical University, Nanning, 530021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guanqiao Jin, Email jinguanqiao77@gxmu.edu.cnBackground: The anti-Programmed Death-Ligand 1 (termed aPD-L1) immune checkpoint blockade therapy has emerged as a promising treatment approach for various advanced solid tumors. However, the effect of aPD-L1 inhibitors limited by the tumor microenvironment makes most patients exhibit immunotherapy resistance.Methods: We conjugated the Sialyl Lewis X with a polyethylene glycol-coated ultrasmall superparamagnetic iron oxide (USPIO-PEG) to form UPS nanoparticles (USPIO-PEG-SLex, termed UPS). The physicochemical properties of UPS were tested and characterized. Transmission electron microscopy and ICP-OES were used to observe the cellular uptake and targeting ability of UPS. Flow cytometry, mitochondrial membrane potential staining, live-dead staining and scratch assay were used to verify the in vitro photothermal effect of UPS, and the stimulation of UPS on immune-related pathways at the gene level was analyzed by sequencing. Biological safety analysis and pharmacokinetic analysis of UPS were performed. Finally, the amplification effect of UPS-mediated photothermal therapy on aPD-L1-mediated immunotherapy and the corresponding mechanism were studied.Results: In vitro experiments showed that UPS had strong photothermal therapy ability and was able to stimulate 5 immune-related pathways. In vivo, when the PTT assisted aPD-L1 treatment, it exhibited a significant increase in CD4+ T cell infiltration by 14.46-fold and CD8+ T cell infiltration by 14.79-fold, along with elevated secretion of tumor necrosis factor-alpha and interferon-gamma, comparing with alone aPD-L1. This PTT assisted aPD-L1 therapy achieved a significant inhibition of both primary tumors and distant tumors compared to the alone aPD-L1, demonstrating a significant difference.Conclusion: The nanotheranostic agent UPS has been introduced into immunotherapy, which has effectively broadened its application in biomedicine. This photothermal therapeutic approach of the UPS nanotheranostic agent enhancing the efficacy of aPD-L1 immune checkpoint blockade therapy, can be instructive to address the challenges associated with immunotherapy resistance, thereby offering potential for clinical translation.Keywords: immunotherapy resistance, immune checkpoint blockade, nanotheranostic agent, photothermal therapy, enhancing efficacy